A fuel cell powered unmanned aerial vehicle for low altitude surveillance missions. (9th March 2017) - Lapeña-Rey, N.; Blanco, J.A.; Ferreyra, E.; Lemus, J.L.; Pereira, S.; Serrot, E.
Abstract: Boeing Research & Technology Europe has designed, developed and subsequently bench and flight tested, in a wide range of different operative conditions, an electric Unmanned Air Vehicle (UAV) powered by a hybrid energy source. The energy source features a 200 We Polymer Electrolyte Membrane (PEM) fuel cell system fed by a chemical hydride hydrogen generator that produces highly pure hydrogen at the fuel cell operating pressure from the controlled hydrolysis of Sodium Borohydride (NaBH4 ), resulting in 900 Wh of energy from 1 L of chemical solution. Equipped also with high specific energy Lithium Polymer batteries, this fuel cell powered UAV is able to achieve flight durations close to 4 h. This paper summarizes the aircraft and systems design, the results of the bench and flight tests along with the main challenges faced during this development and the lessons learned for future optimization. Highlights: Fuel cell powered electric UAV low altitude high endurance flight missions. Off-the-shelf fuel cell technology and chemical hydrides based generator. Challenges encountered in demanding weather conditions for the generator operation.